Liquid crystal display device and polarizing plate
By using polyester film with a specific refractive index and a white light emitting diode as the backlight source in the liquid crystal display device, the problem of rainbow-like color points under the polyester film protection film is solved, and better visual effects and visibility are achieved.
Patent Information
- Application Number
- JP2023121089
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2016-03-16
- Filing Date
- 2023-07-25
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2036-07-11
AI Technical Summary
In a liquid crystal display device, when a polyester film is used as a polarized sheet protective film, a rainbow-like color point still exists when a white light emitting diode is used as a backlight source.
A polyester film with a specific delay is used as the polarization sheet protective film, and a white light emitting diode is used as the backlight source to ensure that the refractive index of the polyester film is controlled between 1.53 and 1.62 in the polarization axis direction, thereby reducing the reflection of light on the film surface.
It effectively reduces the appearance of rainbow-like color dots and improves the visibility and visual effects of display devices.
Smart Images

Figure 0007663109000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a liquid crystal display device and a polarizing plate, and more particularly to a liquid crystal display device and a polarizing plate in which the occurrence of rainbow-like color spots is reduced. [Background technology]
[0002] A polarizing plate used in a liquid crystal display (LCD) is generally constructed by sandwiching a polarizer made of polyvinyl alcohol (PVA) or the like dyed with iodine between two polarizer protective films, and triacetyl cellulose (TAC) films are generally used as the polarizer protective films. In recent years, as LCDs become thinner, there has been a demand for thinner polarizing plates. However, when the thickness of the TAC film used as the protective film is reduced for this purpose, problems arise in that sufficient mechanical strength cannot be obtained and moisture permeability is deteriorated. In addition, TAC films are very expensive, and polyester films have been proposed as an inexpensive alternative material (Patent Documents 1 to 3), but there is a problem in that rainbow-like color spots are observed.
[0003] When an oriented polyester film with birefringence is placed on one side of a polarizer, the linearly polarized light emitted from the backlight unit or polarizer changes its polarization state as it passes through the polyester film. The transmitted light exhibits interference colors specific to the retardation, which is the product of the birefringence and thickness of the oriented polyester film. Therefore, when a cold cathode tube or hot cathode tube with a discontinuous emission spectrum is used as a light source, the transmitted light intensity varies depending on the wavelength, resulting in rainbow-like color spots (see: Proceedings of the 15th Micro-Optical Conference, pages 30-31).
[0004] As a means for solving the above problems, it has been proposed to use a white light source having a continuous and wide emission spectrum, such as a white light emitting diode, as a backlight source, and further to use an oriented polyester film having a certain retardation as a polarizer protective film (Patent Document 4). A white light emitting diode has a continuous and wide emission spectrum in the visible light range. Therefore, it has been proposed that, focusing on the envelope shape of the interference color spectrum of the transmitted light that has passed through a birefringent body, a spectrum similar to the emission spectrum of the light source can be obtained by controlling the retardation of the oriented polyester film, and rainbow spots can be suppressed.
[0005] By making the orientation direction of the oriented polyester film perpendicular or parallel to the polarization direction of the polarizing plate, the linearly polarized light emitted from the polarizer passes through the oriented polyester film while maintaining its polarized state. In addition, by controlling the birefringence of the oriented polyester film to enhance the uniaxial orientation, light incident from an oblique direction also passes through while maintaining its polarized state. When the oriented polyester film is viewed obliquely, there is a shift in the orientation main axis direction compared to when viewed from directly above, but if the uniaxial orientation is high, the shift in the orientation main axis direction when viewed obliquely is small. For this reason, it is considered that the shift between the direction of the linearly polarized light and the orientation main axis direction is small, making it difficult for the polarization state to change. In this way, it was considered that by controlling the emission spectrum of the light source, the orientation state of the birefringent body, and the orientation main axis direction, the change in the polarization state is suppressed, and the visibility is significantly improved without the occurrence of rainbow-like color spots. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2002-116320 A [Patent Document 2] JP 2004-219620 A [Patent Document 3] JP 2004-205773 A [Patent Document 4] WO2011 / 162198 Summary of the Invention [Problem to be solved by the invention]
[0007] In response to the recent growing demand for an expansion of the color gamut of liquid crystal display devices, a white light emitting diode (e.g., a blue light emitting diode) having an emission spectrum with a peak top in each wavelength region of the blue region (400 nm or more and less than 495 nm), the green region (495 nm or more and less than 600 nm), and the red region (600 nm or more and less than 780 nm), and a half width of the peak in the red region (600 nm or more and less than 780 nm) being relatively narrow (less than 5 nm) (e.g., a blue light emitting diode and at least K2SiF6:Mn 4+ Liquid crystal display devices using a backlight source made of a white light emitting diode having a fluoride phosphor such as a fluorine atom or the like have been developed.
[0008] When a liquid crystal display device is industrially produced using a polarizing plate using a polyester film as a polarizer protective film, the transmission axis of the polarizer and the fast axis of the polyester film are usually arranged to be perpendicular to each other. This is because the polyvinyl alcohol film, which is the polarizer, is produced by longitudinal uniaxial stretching, while the polyester film, which is the protective film, is produced by longitudinal stretching and then transverse stretching, so that the orientation main axis direction of the polyester film is transverse, and when a polarizing plate is produced by laminating these long pieces together, the fast axis of the polyester film and the transmission axis of the polarizer are usually perpendicular. In this case, by using an oriented polyester film with a specific retardation as the polyester film and using a light source with a continuous and wide emission spectrum, such as a white LED made of a light-emitting element combining a blue light-emitting diode and a yellow yttrium-aluminum-garnet phosphor as the backlight source, the rainbow-like color spots are greatly improved, but it was discovered that a new problem still exists in that rainbow spots still occur when a backlight source made of a white light-emitting diode with an emission spectrum with a relatively narrow half-width (less than 5 nm) of the peak in the red region (600 nm to 780 nm) is used.
[0009] In other words, the object of the present invention is to provide a liquid crystal display device and a polarizing plate in which iridescence is suppressed even when a polyester film is used as a polarizer protective film in a liquid crystal display device having a backlight light source consisting of a white light-emitting diode having an emission spectrum with peak tops in each of the wavelength regions of the blue region (400 nm or more and less than 495 nm), the green region (495 nm or more and less than 600 nm), and the red region (600 nm or more and less than 780 nm), and with a relatively narrow half-width (less than 5 nm) of the peak in the red region (600 nm or more and less than 780 nm). [Means for solving the problem]
[0010] Representative aspects of the present invention are as follows. Section 1. A liquid crystal display device having a backlight source, two polarizing plates, and a liquid crystal cell disposed between the two polarizing plates, the backlight light source is a white light-emitting diode having an emission spectrum with peak tops in each of the wavelength regions of 400 nm or more and less than 495 nm, 495 nm or more and less than 600 nm, and 600 nm or more and 780 nm or less, and a half-width of a peak with the highest peak intensity in the wavelength region of 600 nm or more and 780 nm or less is less than 5 nm; At least one of the polarizing plates has a polyester film having a retardation of 1500 to 30000 nm laminated on at least one surface of a polarizer, and the refractive index of the polyester film in a direction parallel to the transmission axis of the polarizer is 1.53 to 1.62. LCD display device. Section 2. The emission spectrum of the backlight light source is The half-width of the peak with the highest peak intensity in the wavelength region of 400 nm or more and less than 495 nm is 5 nm or more, The half-width of the peak with the highest peak intensity in the wavelength region of 495 nm or more and less than 600 nm is 5 nm or more. Item 1. A liquid crystal display device according to item 1. Section 3. 3. The liquid crystal display device according to item 1 or 2, wherein a difference between a refractive index of the polarizer in a transmission axis direction and a refractive index of the polyester film in a direction parallel to the transmission axis of the polarizer is 0.12 or less. Section 4. A polarizing plate in which a polyester film having a retardation of 1500 to 30000 nm is laminated on at least one surface of a polarizer, The refractive index of the polyester film in a direction parallel to the transmission axis of the polarizer is 1.53 to 1.62. A polarizing plate for a liquid crystal display device having a backlight light source consisting of a white light-emitting diode having an emission spectrum with peak tops in each of the wavelength regions of 400 nm or more and less than 495 nm, 495 nm or more and less than 600 nm, and 600 nm or more and less than 780 nm, and the half-width of the peak with the highest peak intensity in the wavelength region of 600 nm or more and less than 780 nm is less than 5 nm. Effect of the Invention
[0011] The liquid crystal display device and polarizing plate of the present invention can ensure good visibility with the occurrence of rainbow-like color spots being significantly suppressed at any observation angle. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Generally, a liquid crystal display device is composed of a rear module, a liquid crystal cell, and a front module, in that order from the side facing the backlight light source to the side where an image is displayed (the viewing side). The rear module and the front module are generally composed of a transparent substrate, a transparent conductive film formed on the surface of the liquid crystal cell side, and a polarizing plate arranged on the opposite side. Here, the polarizing plate is arranged on the side facing the backlight light source in the rear module, and on the side where an image is displayed (the viewing side) in the front module.
[0013] The liquid crystal display device of the present invention comprises at least a backlight source, two polarizing plates, and a liquid crystal cell disposed between the two polarizing plates.
[0014] In addition, the liquid crystal display device may have other components, such as a color filter, a lens film, a diffusion sheet, and an anti-reflection film, as appropriate, in addition to the backlight source, the polarizing plate, and the liquid crystal cell. A brightness enhancement film may be provided between the light source side polarizing plate and the backlight source. An example of the brightness enhancement film is a reflective polarizing plate that transmits one linearly polarized light and reflects linearly polarized light perpendicular to the transmitted light. As the reflective polarizing plate, for example, a brightness enhancement film of the DBEF (registered trademark) (Dual Brightness Enhancement Film) series manufactured by Sumitomo 3M Limited is preferably used. The reflective polarizing plate is usually arranged so that the absorption axis of the reflective polarizing plate and the absorption axis of the light source side polarizing plate are parallel to each other.
[0015] At least one of the two polarizing plates arranged in the liquid crystal display device is a polarizer dyed with iodine such as polyvinyl alcohol (PVA) on at least one surface of which a polyester film is laminated. The refractive index of the polyester film in the direction parallel to the transmission axis of the polarizer is preferably 1.53 to 1.62. A film having no birefringence, such as a TAC film, an acrylic film, or a norbornene-based film, is preferably laminated on the other surface of the polarizer (three-layer polarizing plate), but it is not necessary to laminate a film on the other surface of the polarizer (two-layer polarizing plate). When polyester films are used as protective films on both sides of the polarizer, it is preferable that the slow axes of both polyester films are approximately parallel to each other.
[0016] The polarizer can be appropriately selected from any polarizer (polarizing film) used in the technical field. A representative polarizer can be a polyvinyl alcohol film or the like dyed with a dichroic material such as iodine, but is not limited thereto, and any publicly known or future developed polarizer can be appropriately selected and used.
[0017] The PVA film may be a commercially available product, such as Kuraray Vinylon (manufactured by Kuraray Co., Ltd.), Tohcello Vinylon (manufactured by Tohcello Co., Ltd.), or Nihon Vinylon (manufactured by Nippon Synthetic Chemical Industry Co., Ltd.). Examples of dichroic materials include iodine, diazo compounds, polymethine dyes, and the like.
[0018] The polarizer can be obtained by any method, for example, by uniaxially stretching a PVA film dyed with a dichroic material in an aqueous solution of boric acid, and washing and drying while maintaining the stretched state. The stretching ratio of the uniaxial stretching is usually about 4 to 8 times, but is not particularly limited. Other manufacturing conditions, etc. can be appropriately set according to known methods.
[0019] The backlight may be of an edge light type or a direct type, with a light guide plate, a reflector, or the like as a component. In the present invention, the backlight light source of the liquid crystal display device is preferably a white light emitting diode having an emission spectrum with a peak top in each of the wavelength regions of 400 nm to less than 495 nm, 495 nm to less than 600 nm, and 600 nm to less than 780 nm, and a half width of the peak with the highest peak intensity in the wavelength region of 600 nm to 780 nm is less than 5 nm. The upper limit of the half width of the peak with the highest peak intensity in the wavelength region of 600 nm to 780 nm is preferably less than 5 nm, more preferably less than 4 nm, and even more preferably less than 3.5 nm. The lower limit is preferably 1 nm or more, more preferably 1.5 nm or more. If the half width of the peak is less than 5 nm, the color gamut of the liquid crystal display device is expanded, which is preferable. If the half width of the peak is less than 1 nm, the light emission efficiency may be deteriorated, which is not preferable. The shape of the emission spectrum is designed based on the balance between the required color gamut and luminous efficiency. Note that the half-width here refers to the peak width (nm) at half the intensity of the peak intensity at the wavelength of the peak top.
[0020] The application of a backlight source with an emission spectrum having the above-mentioned characteristics to LCDs is a technology that has attracted attention in recent years due to the growing demand for an expanded color gamut. Conventional white LEDs (e.g., light-emitting elements that combine a blue light-emitting diode with an yttrium-aluminum-garnet yellow phosphor) are used as backlight sources, but LEDs can only reproduce about 20% of the colors in the spectrum that the human eye can recognize. In contrast, it is said that if a backlight source with an emission spectrum having the above-mentioned characteristics is used, it will be possible to reproduce more than 60% of the colors.
[0021] The wavelength range of 400 nm or more and less than 495 nm is more preferably 430 nm or more and less than 470 nm. The wavelength range of 495 nm or more and less than 600 nm is more preferably 510 nm or more and less than 560 nm. The wavelength range of 600 nm or more and less than 780 nm is more preferably 600 nm or more and less than 700 nm, and even more preferably 610 nm or more and less than 680 nm.
[0022] The half-width of the peak at the top of the peak in each wavelength region of 400 nm or more and less than 495 nm, and 495 nm or more and less than 600 nm of the emission spectrum (half-width of the peak with the highest peak intensity in each wavelength region) is not particularly limited, but the half-width of the peak with the highest peak intensity in the wavelength region of 400 nm or more and less than 495 nm is preferably 5 nm or more, and the half-width of the peak with the highest peak intensity in the wavelength region of 495 nm or more and less than 600 nm is preferably 5 nm or more. From the viewpoint of ensuring an appropriate color gamut, the upper limit of the half-width of the peak at the top of the peak in each wavelength region of 400 nm or more and less than 495 nm, and 495 nm or more and less than 600 nm (half-width of the peak with the highest peak intensity in each wavelength region) is preferably 140 nm or less, preferably 120 nm or less, preferably 100 nm or less, more preferably 80 nm or less, even more preferably 60 nm or less, and even more preferably 50 nm or less.
[0023] A specific example of a white light source having an emission spectrum with the above-mentioned characteristics is a phosphor type white light emitting diode that combines a blue light emitting diode and a phosphor. 4+ Examples of the Mn4+-activated fluoride complex phosphor include Mn 4+ It is a phosphor that uses as an activator a fluoride complex salt of an alkali metal, amine or alkaline earth metal as a host crystal. The fluoride complexes that form the host crystal include those with a coordination center of a trivalent metal (B, Al, Ga, In, Y, Sc, lanthanides), a tetravalent metal (Si, Ge, Sn, Ti, Zr, Re, Hf), or a pentavalent metal (V, P, Nb, Ta), and the number of fluorine atoms coordinated around them is 5 to 7.
[0024] Mn 4+ Suitable examples of activated fluoride complex phosphors include A2[MF6]:Mn (A is one or more selected from Li, Na, K, Rb, Cs, and NH4; M is one or more selected from Ge, Si, Sn, Ti, and Zr), E[MF6]:Mn (E is one or more selected from Mg, Ca, Sr, Ba, and Zn; M is one or more selected from Ge, Si, Sn, Ti, and Zr), Ba 0.65 , Zr 0.35 F 2.70 :Mn, A3[ZrF7]:Mn (A is one or more selected from Li, Na, K, Rb, Cs, NH4), A2[MF5]:Mn (A is one or more selected from Li, Na, K, Rb, Cs, NH4; M is one or more selected from Al, Ga, In), A3[MF6]:Mn (A is one or more selected from Li, Na, K, Rb, Cs, NH4; M is one or more selected from Al, Ga, In), Zn2[MF7]:Mn (M is one or more selected from Al, Ga, In), A[In2F7]:Mn (A is one or more selected from Li, Na, K, Rb, Cs, NH4).
[0025] Preferred Mn 4+One of the activated fluoride complex phosphors is A2MF6:Mn (A is one or more selected from Li, Na, K, Rb, Cs, and NH4; M is one or more selected from Ge, Si, Sn, Ti, and Zr) which uses a hexafluoro complex salt of an alkali metal as a host crystal. Among them, A is one or more selected from K (potassium) or Na (sodium), and M is Si (silicon) or Ti (titanium). Among them, A is particularly preferably K (the ratio of K to the total amount of A is 99 mol % or more) and M is Si. The activating element is preferably 100% Mn (manganese), but Ti, Zr, Ge, Sn, Al, Ga, B, In, Cr, Fe, Co, Ni, Cu, Nb, Mo, Ru, Ag, Zn, Mg, etc. may be contained within a range of less than 10 mol % of the total amount of the activating element. When M is Si, the ratio of Mn in the total of Si and Mn is preferably within the range of 0.5 mol % to 10 mol %. 2+x M y Mn z F n (A is Na or K; M is Si or Al; -1≦x≦1, 0.9≦y+z≦1.1, 0.001≦z≦0.4, and 5≦n≦7).
[0026] The backlight light source is preferably a blue light emitting diode and a white light emitting diode having at least a fluoride phosphor as a phosphor, and more preferably a blue light emitting diode and at least K2SiF6:Mn 4+ For example, a commercially available white LED such as NSSW306FT manufactured by Nichia Corporation can be used.
[0027] Among the phosphors, examples of green phosphors include sialon phosphors having a basic composition such as β-SiAlON:Eu, silicate phosphors having a basic composition such as (Ba,Sr)2SiO4:Eu, and others.
[0028] When multiple peaks exist in any of the wavelength regions of 400 nm or more and less than 495 nm, 495 nm or more and less than 600 nm, or 600 nm or more and 780 nm or less, they are considered as follows. When the multiple peaks are independent from each other, it is preferable that the half-width of the peak with the highest peak intensity is in the above range. Furthermore, it is more preferable that the half-width of other peaks having an intensity of 70% or more of the highest peak intensity is also in the above range. For an independent peak having a shape in which multiple peaks overlap, if the half-width of the peak with the highest peak intensity among the multiple peaks can be measured as is, the half-width is used. Here, an independent peak is one that has an area with an intensity of 1 / 2 the peak intensity on both the short wavelength side and the long wavelength side of the peak. In other words, when multiple peaks overlap and each peak does not have an area with an intensity of 1 / 2 the peak intensity on both sides, the multiple peaks are regarded as a single peak as a whole. For such a single peak having a shape in which multiple peaks overlap, the half-width is the width (nm) of the peak at 1 / 2 the intensity of the highest peak among them. Among the multiple peaks, the peak with the highest peak intensity is defined as the peak top. In addition, it is preferable that the peaks having the highest peak intensity in each of the wavelength regions of 400 nm to less than 495 nm, 495 nm to less than 600 nm, and 600 nm to 780 nm are independent of the peaks in the other wavelength regions. In particular, it is preferable in terms of color vividness that there is a region between the peak having the highest peak intensity in the wavelength region of 495 nm to less than 600 nm and the peak having the highest peak intensity in the wavelength region of 600 nm to 780 nm, in which the intensity is 1 / 3 of the peak intensity of the peak having the highest peak intensity in the wavelength region of 600 nm to 780 nm.
[0029] The emission spectrum of the backlight light source can be measured using a spectrometer such as the multichannel spectrometer PMA-12 manufactured by Hamamatsu Photonics.
[0030] As a result of intensive research, the inventors of the present invention have found that in a liquid crystal display device having a backlight light source consisting of white light emitting diodes with emission spectrum peak tops in the respective wavelength regions of the blue region (400 nm or more and less than 495 nm), the green region (495 nm or more and less than 600 nm), and the half width of the peak in the red region (600 nm or more and less than 780 nm) is relatively narrow at less than 5 nm, as in the above-mentioned backlight light source, even when a polarizing plate using a polyester film as a polarizer protective film is used, as long as the refractive index of the polyester film in the direction parallel to the transmission axis of the polarizer constituting the polarizing plate is in the range of 1.53 to 1.62. The mechanism by which the occurrence of rainbow-like color spots is suppressed by the above-mentioned embodiment is considered to be as follows.
[0031] When an oriented polyester film is arranged on one side of a polarizer, the polarization state of the linearly polarized light emitted from the backlight unit or the polarizer changes when passing through the polyester film. One of the factors that may cause the polarization state to change is the refractive index difference at the interface between the air layer and the oriented polyester film, or the refractive index difference at the interface between the polarizer and the oriented polyester film. When the linearly polarized light that is incident on the oriented polyester film passes through each interface, a part of the light is reflected due to the refractive index difference at the interface. At this time, the polarization state of both the emitted light and the reflected light changes, which is considered to be one of the factors that cause the rainbow-like color spots to occur. Therefore, it is considered that by reducing the refractive index difference between the air layer and the oriented polyester film, and the refractive index difference between the polarizer and the oriented polyester film in the polarization direction (transmission axis direction) of the incident linearly polarized light, reflection at each interface is suppressed, and the rainbow-like color spots are suppressed. In order to reduce the refractive index difference between the air layer and the oriented polyester film, and between the polarizer and the oriented polyester film in the polarization direction (transmission axis direction) of the incident linearly polarized light, this can be achieved by adjusting the refractive index of the polyester film in the direction parallel to the transmission axis to a low value of approximately 1.53 to 1.62.
[0032] As described above, in the present invention, in a liquid crystal display device having a backlight light source consisting of a white light-emitting diode having an emission spectrum peak top in each of the wavelength regions of the blue region (400 nm or more and less than 495 nm), the green region (495 nm or more and less than 600 nm), and the red region (600 nm or more and 780 nm or less), and having a relatively narrow half-width of the peak in the red region (600 nm or more and 780 nm) of less than 5 nm, even if a polarizing plate using a polyester film as a polarizer protective film is used, it is possible to achieve good visibility without the occurrence of rainbow color spots.
[0033] In the polarizing plate of the present invention, a polarizer protective film made of a polyester film is laminated on at least one surface of the polarizer. The refractive index of the polyester film in the direction parallel to the transmission axis direction of the polarizer is preferably adjusted to a low value in the range of 1.53 to 1.62. This makes it possible to suppress reflection at the interface between the air layer and the polyester film and the interface between the polarizer and the polyester film, and to suppress rainbow-like color spots. If the refractive index exceeds 1.62, rainbow-like color spots may occur when observed from an oblique direction. It is preferably 1.61 or less, more preferably 1.60 or less, even more preferably 1.59 or less, and even more preferably 1.58 or less.
[0034] On the other hand, the lower limit of the refractive index is 1.53. If the refractive index is less than 1.53, the crystallization of the polyester film becomes insufficient, and the properties obtained by stretching, such as dimensional stability, mechanical strength, and chemical resistance, become insufficient, which is not preferable. The refractive index is preferably 1.54 or more, more preferably 1.55 or more, even more preferably 1.56 or more, and even more preferably 1.57 or more.
[0035] In order to set the refractive index of the polyester film in the direction parallel to the transmission axis direction of the polarizer to the range of 1.53 to 1.62, the polarizing plate of the present invention is preferably such that the transmission axis of the polarizer and the fast axis (perpendicular to the slow axis) of the polyester film are approximately parallel. The refractive index of the polyester film in the fast axis direction (perpendicular to the slow axis) can be adjusted to the range of 1.53 to 1.62 by a stretching treatment in the film-forming process described later. By making the fast axis direction of the polyester film and the transmission axis direction of the polarizer approximately parallel, a polarizing plate having a refractive index of the polyester film in the direction parallel to the transmission axis direction of the polarizer of 1.53 to 1.62 can be manufactured. Here, approximately parallel means that the angle between the transmission axis of the polarizer and the fast axis of the polarizer protective film is preferably -15° to 15°, more preferably -10° to 10°, even more preferably -5° to 5°, still more preferably -3° to 3°, even more preferably -2° to 2°, and particularly preferably -1° to 1°. In a preferred embodiment, "almost parallel" means "substantially parallel." Here, "substantially parallel" means that the transmission axis and the fast axis are parallel to a degree that allows for the deviation that inevitably occurs when the polarizer and the protective film are bonded together. The direction of the slow axis can be measured using a molecular orientation meter (e.g., MOA-6004 type molecular orientation meter manufactured by Oji Scientific Instruments Co., Ltd.).
[0036] In other words, the refractive index in the fast axis direction of the polyester film used in the present invention is preferably 1.53 or more and 1.62 or less, and by laminating the polyester film so that the transmission axis of the polarizer and the fast axis of the polyester film are approximately parallel, a polarizing plate can be produced in which the refractive index of the polyester film in the direction parallel to the transmission axis of the polarizer is 1.53 or more and 1.62 or less.
[0037] The difference between the refractive index in the transmission axis direction of the polarizer constituting the polarizing plate and the refractive index of the polyester film in the direction parallel to the transmission axis of the polarizer is preferably 0.12 or less, more preferably 0.10 or less, more preferably 0.09 or less, more preferably 0.08 or less, more preferably 0.07 or less, more preferably 0.06 or less, and more preferably 0.05 or less. The smaller the refractive index difference, the more suppressed the reflection at the interface of the polyester film and the more suppressed the rainbow spots, which is preferable. The lower limit is 0.
[0038] The polarizer is not particularly limited, and may be a conventionally known polarizer, such as one obtained by dyeing iodine on polyvinyl alcohol (PVA), etc. The refractive index of the polarizer in the transmission axis direction is preferably 1.41 to 1.56, more preferably 1.44 to 1.55, and even more preferably 1.47 to 1.54.
[0039] In addition, the polyester film used for the polarizer protective film preferably has a retardation of 1500 to 30000 nm. If the retardation is in the above range, it is preferable because it tends to be easier to reduce rainbow spots. The preferred lower limit of the retardation is 3000 nm, the next preferred lower limit is 3500 nm, the more preferred lower limit is 4000 nm, the even more preferred lower limit is 6000 nm, and the even more preferred lower limit is 8000 nm. The preferred upper limit is 30000 nm, and polyester films having a retardation greater than this tend to be significantly thicker and less easy to handle as industrial materials.
[0040] The retardation can be obtained by measuring the refractive index and thickness in two perpendicular axial directions on the film, or by using a commercially available automatic birefringence measuring device such as KOBRA-21ADH (Oji Scientific Instruments Co., Ltd.). The refractive index can be obtained by an Abbe refractometer (measurement wavelength 589 nm).
[0041] The ratio (Re / Rth) of the retardation (Re: in-plane retardation) of the polyester film to the retardation in the thickness direction (Rth) is preferably 0.2 or more, more preferably 0.5 or more, and even more preferably 0.6 or more. The larger the ratio (Re / Rth) of the retardation to the thickness direction retardation, the more isotropic the birefringence action becomes, and the less likely it is that rainbow-like color spots will occur depending on the observation angle. In a completely uniaxial (symmetrical) film, the ratio (Re / Rth) of the retardation to the thickness direction retardation is 2.0, so the upper limit of the ratio (Re / Rth) of the retardation to the thickness direction retardation is preferably 2.0. The thickness direction retardation means the average of the retardation obtained by multiplying the two birefringences ΔNxz and ΔNyz by the film thickness d when the film is viewed from the thickness direction cross section.
[0042] The above-mentioned polyester film-made polarizer protective film can be used for polarizing plates on both the incident light side (light source side) and the outgoing light side (viewing side). In a polarizing plate arranged on the incident light side, the above-mentioned polyester film-made polarizer protective film may be arranged on the incident light side, on the liquid crystal cell side, or on both sides, with the polarizer as the starting point, but is preferably arranged on at least the incident light side. In a polarizing plate arranged on the outgoing light side, the above-mentioned polyester film-made polarizer protective film may be arranged on the liquid crystal side, on the outgoing light side, or on both sides, with the polarizer as the starting point, but is preferably arranged on at least the outgoing light side.
[0043] The polyester used in the polyester film may be polyethylene terephthalate or polyethylene naphthalate, but may contain other copolymerization components. These resins are excellent in transparency and thermal and mechanical properties, and retardation can be easily controlled by stretching. In particular, polyethylene terephthalate is the most suitable material because it has a large inherent birefringence, and the refractive index in the fast axis direction (perpendicular to the slow axis direction) can be kept low by stretching the film, and a large retardation can be obtained relatively easily even if the film is thin.
[0044] In addition, in order to suppress deterioration of optically functional dyes such as iodine dyes, the polyester film desirably has a light transmittance of 20% or less at a wavelength of 380 nm. The light transmittance of 380 nm is more preferably 15% or less, even more preferably 10% or less, and particularly preferably 5% or less. If the light transmittance is 20% or less, deterioration of the optically functional dye caused by ultraviolet rays can be suppressed. The transmittance is measured in a direction perpendicular to the plane of the film, and can be measured using a spectrophotometer (e.g., Hitachi U-3500 type).
[0045] In order to make the transmittance of the polyester film at a wavelength of 380 nm 20% or less, it is desirable to appropriately adjust the type and concentration of the ultraviolet absorber and the thickness of the film. The ultraviolet absorber used in the present invention is a known substance. Examples of ultraviolet absorbers include organic ultraviolet absorbers and inorganic ultraviolet absorbers, and from the viewpoint of transparency, organic ultraviolet absorbers are preferred. Examples of organic ultraviolet absorbers include benzotriazole-based, benzophenone-based, cyclic imino ester-based, and combinations thereof, but are not particularly limited as long as they are within the above-mentioned absorbance range. However, from the viewpoint of durability, benzotriazole-based and cyclic imino ester-based are particularly preferred. When two or more types of ultraviolet absorbers are used in combination, ultraviolet rays of different wavelengths can be absorbed simultaneously, so that the ultraviolet absorption effect can be further improved.
[0046] Examples of benzophenone-based ultraviolet absorbers, benzotriazole-based ultraviolet absorbers, and acrylonitrile-based ultraviolet absorbers include 2-[2'-hydroxy-5'-(methacryloyloxymethyl)phenyl]-2H-benzotriazole, 2-[2'-hydroxy-5'-(methacryloyloxyethyl)phenyl]-2H-benzotriazole, 2-[2'-hydroxy-5'-(methacryloyloxypropyl)phenyl]-2H-benzotriazole, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, 2,4-di-tert-butyl-6-(5-chlorobenzotriazol-2-yl)phenol, 2-(2'-hydroxy-3'-tert -butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(5-chloro(2H)-benzotriazol-2-yl)-4-methyl-6-(tert-butyl)phenol, 2,2'-methylenebis(4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol, etc. Examples of cyclic imino ester-based ultraviolet absorbers include 2,2'-(1,4-phenylene)bis(4H-3,1-benzoxazinon-4-one), 2-methyl-3,1-benzoxazin-4-one, 2-butyl-3,1-benzoxazin-4-one, 2-phenyl-3,1-benzoxazin-4-one, etc., but are not particularly limited thereto.
[0047] In addition, in addition to the ultraviolet absorber, it is also a preferred embodiment to contain various additives other than the catalyst within a range that does not impair the effects of the present invention. Examples of additives include inorganic particles, heat-resistant polymer particles, alkali metal compounds, alkaline earth metal compounds, phosphorus compounds, antistatic agents, light-resistant agents, flame retardants, heat stabilizers, antioxidants, gelling inhibitors, surfactants, etc. In addition, in order to achieve high transparency, it is also preferable that the polyester film does not substantially contain particles. "Substantially does not contain particles" means, for example, in the case of inorganic particles, a content that is 50 ppm or less, preferably 10 ppm or less, and particularly preferably below the detection limit when inorganic elements are quantified by fluorescent X-ray analysis.
[0048] It is also a preferred embodiment that various functional layers, i.e., a hard coat layer, an antiglare layer, an antireflection layer, etc., are provided on the surface of the polyester film, which is the polarizer protective film used in the present invention, for the purpose of preventing reflection, suppressing glare, suppressing scratches, etc. When providing various functional layers, it is preferable that the polyester film has an easy-adhesion layer on its surface. In this case, from the viewpoint of suppressing interference due to reflected light, it is preferable to adjust the refractive index of the easy-adhesion layer so that it is close to the geometric mean of the refractive index of the functional layer and the refractive index of the polyester film. The refractive index of the easy-adhesion layer can be adjusted by a known method, and can be easily adjusted, for example, by adding titanium, germanium, or other metal species to the binder resin.
[0049] The polyester film may be subjected to corona treatment, coating treatment, flame treatment, or the like in order to improve adhesion to the polarizer.
[0050] In the present invention, in order to improve the adhesion to the polarizer, it is preferable that at least one surface of the film of the present invention has an easy-adhesion layer mainly composed of at least one of polyester resin, polyurethane resin, and polyacrylic resin. Here, the "main component" refers to a component that is 50% by mass or more of the solid components constituting the easy-adhesion layer. The coating liquid used to form the easy-adhesion layer of the present invention is preferably an aqueous coating liquid containing at least one of water-soluble or water-dispersible copolymer polyester resin, acrylic resin, and polyurethane resin. Examples of these coating liquids include water-soluble or water-dispersible copolymer polyester resin solutions, acrylic resin solutions, and polyurethane resin solutions disclosed in Japanese Patent No. 3567927, Japanese Patent No. 3589232, Japanese Patent No. 3589233, Japanese Patent No. 3900191, and Japanese Patent No. 4150982.
[0051] The easy-adhesion layer can be obtained by applying the coating liquid to one or both sides of a uniaxially stretched film in the longitudinal direction, drying the film at 100 to 150°C, and then stretching the film in the transverse direction. The final coating amount of the easy-adhesion layer is preferably controlled to 0.05 to 0.20 g / m2. 2 If the coating amount is less than 0.20 g / m, the adhesion to the obtained polarizer may be insufficient. 2 When the easy-adhesion layer is provided on both sides of the polyester film, the coating amounts of the easy-adhesion layers on both sides may be the same or different, and each can be independently set within the above range.
[0052] It is preferable to add particles to the easy-adhesion layer to give it easy slipperiness. It is preferable to use particles with an average particle size of 2 μm or less. If the average particle size of the particles exceeds 2 μm, the particles are likely to fall off from the coating layer. Examples of particles to be contained in the easy-adhesion layer include inorganic particles such as titanium oxide, barium sulfate, calcium carbonate, calcium sulfate, silica, alumina, talc, kaolin, clay, calcium phosphate, mica, hectorite, zirconia, tungsten oxide, lithium fluoride, and calcium fluoride, and organic polymer particles such as styrene-based, acrylic-based, melamine-based, benzoguanamine-based, and silicone-based particles. These may be added to the easy-adhesion layer alone, or two or more types may be added in combination.
[0053] The coating liquid can be applied by any known method, such as reverse roll coating, gravure coating, kiss coating, roll brushing, spray coating, air knife coating, wire bar coating, and pipe doctor coating, which can be used alone or in combination.
[0054] The average particle size of the above particles is measured by the following method: Particles are photographed with a scanning electron microscope (SEM), and the maximum diameters (the distance between the two most distant points) of 300 to 500 particles are measured at a magnification such that the size of the smallest particle is 2 to 5 mm, and the average value is taken as the average particle size.
[0055] The polyester film used as the polarizer protective film can be produced according to a general method for producing a polyester film, for example, by melting a polyester resin, extruding the non-oriented polyester into a sheet, stretching the sheet in the longitudinal direction at a temperature equal to or higher than the glass transition temperature by utilizing the speed difference between rolls, stretching the sheet in the transverse direction by a tenter, and then subjecting the sheet to a heat treatment.
[0056] The polyester film used in the present invention may be either a uniaxially stretched film or a biaxially stretched film. However, when a biaxially stretched film is used as a polarizer protective film, rainbow-like color spots are not observed when observed from directly above the film surface, but rainbow-like color spots may be observed when observed from an oblique direction, so care must be taken.
[0057] Specifically, the film-forming conditions of the polyester film are as follows: the longitudinal stretching temperature and the transverse stretching temperature are preferably 80 to 135°C, more preferably 80 to 130°C, and particularly preferably 90 to 120°C. In order to orient the film so that the slow axis is in the TD direction, the longitudinal stretching ratio is preferably 1.0 to 3.5 times, and particularly preferably 1.0 to 3.0 times. In addition, the transverse stretching ratio is preferably 2.5 to 6.0 times, and particularly preferably 3.0 to 5.5 times. In order to orient the film so that the slow axis is in the MD direction, the longitudinal stretching ratio is preferably 2.5 to 6.0 times, and particularly preferably 3.0 to 5.5 times. In addition, the transverse stretching ratio is preferably 1.0 to 3.5 times, and particularly preferably 1.0 to 3.0 times. In order to control the refractive index or retardation in the fast axis direction of the polyester film within the above range, it is preferable to control the ratio of the longitudinal stretching ratio to the transverse stretching ratio. If the difference between the longitudinal and transverse stretching ratios is too small, the refractive index in the fast axis direction of the polyester film tends to exceed 1.62, and it is also difficult to increase the retardation, which is not preferable. In addition, setting the stretching temperature low is a preferable measure for increasing the retardation. In the subsequent heat treatment, the treatment temperature is preferably 100 to 250°C, particularly preferably 180 to 245°C. In order to suppress the fluctuation of retardation, it is preferable that the thickness unevenness of the film is small. Since the stretching temperature and stretching ratio have a large effect on the thickness unevenness of the film, it is necessary to optimize the film-forming conditions from the viewpoint of the thickness unevenness as well. In particular, if the longitudinal stretching ratio is lowered in order to increase the retardation, the longitudinal thickness unevenness may worsen. Since the longitudinal thickness unevenness becomes extremely worse in a certain range of the stretching ratio, it is desirable to set the film-forming conditions outside this range. The thickness unevenness of the polyester film is preferably 5.0% or less, more preferably 4.5% or less, even more preferably 4.0% or less, and particularly preferably 3.0% or less.
[0058] As described above, in order to control the retardation of the polyester film within a specific range, it can be performed by appropriately setting the stretching ratio, stretching temperature, and film thickness. For example, the higher the stretching ratio, the lower the stretching temperature, and the thicker the film, the easier it is to obtain a high retardation. Conversely, the lower the stretching ratio, the higher the stretching temperature, and the thinner the film, the easier it is to obtain a low retardation. However, if the film thickness is increased, the thickness direction phase difference tends to increase. Therefore, it is desirable to appropriately set the film thickness within the range described below. In addition to controlling the retardation, it is necessary to set the final film formation conditions taking into account the physical properties required for processing.
[0059] The thickness of the polyester film is arbitrary, but is preferably in the range of 15 to 300 μm, and more preferably in the range of 15 to 200 μm. In principle, it is possible to obtain a retardation of 1500 nm or more even with a film having a thickness of less than 15 μm. However, in that case, the anisotropy of the mechanical properties of the film becomes significant, and it becomes easy to cause tears, breaks, etc., and the practicality as an industrial material is significantly reduced. A particularly preferable lower limit of the thickness is 25 μm. On the other hand, if the upper limit of the thickness of the polarizer protective film exceeds 300 μm, the thickness of the polarizing plate becomes too thick, which is not preferable. From the viewpoint of practicality as a polarizer protective film, the upper limit of the thickness is preferably 200 μm. A particularly preferable upper limit of the thickness is 100 μm, which is about the same as that of a general TAC film. In order to control the retardation within the range of the present invention even in the above thickness range, the polyester used as the film substrate is preferably polyethylene terephthalate.
[0060] As a method for incorporating an ultraviolet absorber into a polyester film, a combination of known methods can be adopted. For example, the ultraviolet absorber can be incorporated by a method in which a dried ultraviolet absorber is blended in advance with a polymer raw material using a kneading extruder to prepare a master batch, and then a predetermined master batch is mixed with the polymer raw material during film formation.
[0061] In this case, the concentration of the ultraviolet absorber in the master batch is preferably 5 to 30% by mass in order to disperse the ultraviolet absorber uniformly and to compound economically. The conditions for preparing the master batch are preferably a kneading extruder, and the extrusion temperature is preferably a temperature between the melting point of the polyester raw material and 290°C or less, and extrusion is performed for 1 to 15 minutes. If the temperature exceeds 290°C, the amount of the ultraviolet absorber is significantly reduced, and the viscosity of the master batch is significantly reduced. If the extrusion time is less than 1 minute, it becomes difficult to mix the ultraviolet absorber uniformly. At this time, a stabilizer, a color tone adjuster, and an antistatic agent may be added as necessary.
[0062] It is also preferable to make the polyester film have a multi-layer structure of at least three layers, and to add an ultraviolet absorber to the intermediate layer of the film. A three-layer film containing an ultraviolet absorber in the intermediate layer can be specifically produced as follows. A polyester pellet alone for the outer layer, and a master batch containing an ultraviolet absorber and a polyester pellet for the intermediate layer are mixed in a predetermined ratio, dried, and then fed to a known melt lamination extruder, extruded into a sheet from a slit-shaped die, and cooled and solidified on a casting roll to produce an unstretched film. That is, using two or more extruders, a three-layer manifold or a merging block (for example, a merging block having a square merging portion), the film layers constituting both outer layers and the film layer constituting the intermediate layer are laminated, the three-layer sheet is extruded from the die, and cooled with a casting roll to produce an unstretched film. In addition, in order to remove foreign matter contained in the raw polyester that causes optical defects, it is preferable to perform high-precision filtration during melt extrusion. The filtration particle size (initial filtration efficiency 95%) of the filter material used for high-precision filtration of the molten resin is preferably 15 μm or less. If the filtering particle size of the filter medium exceeds 15 μm, the removal of foreign matter of 20 μm or more tends to be insufficient. EXAMPLES
[0063] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples, and can be practiced with appropriate modifications within the scope of the invention, all of which are included in the technical scope of the present invention. The methods for evaluating physical properties in the following examples are as follows.
[0064] (1) Refractive index of polyester film The slow axis direction of the film was determined using a molecular orientation meter (MOA-6004 type molecular orientation meter manufactured by Oji Measurement Instruments Co., Ltd.), and a rectangle of 4 cm x 2 cm was cut out so that the slow axis direction was parallel to the long side of the measurement sample, and used as a measurement sample. The refractive indexes of the two orthogonal axes (refractive index in the slow axis direction: Ny, fast axis (refractive index in the direction perpendicular to the slow axis direction): Nx) and the refractive index in the thickness direction (Nz) of this sample were determined using an Abbe refractometer (NAR-4T manufactured by Atago Co., Ltd., measurement wavelength 589 nm).
[0065] (2) Retardation (Re) Retardation is a parameter defined as the product (ΔNxy×d) of the refractive index anisotropy of two orthogonal axes on a film (ΔNxy=|Nx-Ny|) and the film thickness d (nm), and is a measure of optical isotropy and anisotropy. The biaxial refractive index anisotropy (ΔNxy) was determined by the following method. The slow axis direction of the film was determined using a molecular orientation meter (MOA-6004 molecular orientation meter, manufactured by Oji Measurement Instruments Co., Ltd.), and a 4 cm×2 cm rectangle was cut out so that the slow axis direction was parallel to the long side of the measurement sample, and used as the measurement sample. For this sample, the refractive indexes of two orthogonal axes (refractive index in the slow axis direction: Ny, refractive index in the direction perpendicular to the slow axis direction: Nx) and the refractive index in the thickness direction (Nz) were measured using an Abbe refractometer (Atago Co., Ltd., NAR-4T, measurement wavelength 589 nm), and the absolute value of the difference in refractive index between the two axes (|Nx-Ny|) was taken as the refractive index anisotropy (ΔNxy). The film thickness d (nm) was measured using an electric micrometer (Fine Leuf Co., Ltd., Millitron 1245D) and converted to nm. The retardation (Re) was calculated from the product (ΔNxy×d) of the refractive index anisotropy (ΔNxy) and the film thickness d (nm).
[0066] (3) Thickness retardation (Rth) The thickness retardation is a parameter that indicates the average retardation obtained by multiplying the two birefringences ΔNxz (=|Nx-Nz|) and ΔNyz (=|Ny-Nz|) when viewed from the cross section of the film thickness direction by the film thickness d. Nx, Ny, Nz and the film thickness d (nm) were obtained in the same manner as in the retardation measurement, and the average value of (ΔNxz×d) and (ΔNyz×d) was calculated to obtain the thickness retardation (Rth).
[0067] (4) Measurement of the emission spectrum of the backlight light source The liquid crystal display device used in each example was a REGZA 43J10X manufactured by Toshiba Corporation. When the emission spectrum of the backlight light source (white light emitting diode) of this liquid crystal display device was measured using a multichannel spectrometer PMA-12 manufactured by Hamamatsu Photonics, an emission spectrum having peak tops near 450 nm, 535 nm, and 630 nm was observed. The half-width of each peak top (half-width of the peak having the highest peak intensity in each wavelength region) was 17 nm for the 450 nm peak, 45 nm for the 535 nm peak, and 2 nm for the 630 nm peak, respectively. Note that this light source had multiple peaks in the wavelength region of 600 nm to 780 nm, but the half-width was evaluated at the peak near 630 nm, which has the highest peak intensity in this region. In addition, the exposure time during spectrum measurement was 20 msec.
[0068] (5) Iridescence observation The liquid crystal display device obtained in each Example was visually observed in a dark place from the front and from an oblique direction, and the occurrence of rainbow spots was judged as follows.
[0069] ○: No rainbow spots observed △: Slight rainbow spots observed ×: Iridescence observed ××: Iridescence is significantly observed
[0070] (6) Refractive index of polarizer The refractive index in the transmission axis direction of the polarizer was measured with an Abbe refractometer (NAR-4T SOLID, manufactured by Atago Co., Ltd., measuring wavelength 589 nm).
[0071] (Production Example 1-Polyester A) When the temperature of the esterification reactor reached 200°C, 86.4 parts by mass of terephthalic acid and 64.6 parts by mass of ethylene glycol were charged, and 0.017 parts by mass of antimony trioxide, 0.064 parts by mass of magnesium acetate tetrahydrate, and 0.16 parts by mass of triethylamine were charged as catalysts while stirring. Next, the temperature was increased under pressure and a pressure esterification reaction was carried out under conditions of a gauge pressure of 0.34 MPa and 240°C, after which the esterification reactor was returned to normal pressure and 0.014 parts by mass of phosphoric acid was added. Further, the temperature was increased to 260°C over 15 minutes, and 0.012 parts by mass of trimethyl phosphate was added. Next, after 15 minutes, a dispersion treatment was carried out using a high-pressure disperser, and after 15 minutes, the obtained esterification reaction product was transferred to a polycondensation reactor and a polycondensation reaction was carried out under reduced pressure at 280°C.
[0072] After the polycondensation reaction was completed, the mixture was filtered using a Naslon filter with a 95% cut diameter of 5 μm, extruded from a nozzle in the form of a strand, cooled and solidified using cooling water that had been previously filtered (pore diameter: 1 μm or less), and cut into pellets. The intrinsic viscosity of the resulting polyethylene terephthalate resin (A) was 0.62 dl / g, and it contained substantially no inert particles or internally precipitated particles. (Hereinafter, this will be abbreviated as PET (A)).
[0073] (Production Example 2 - Polyester B) 10 parts by mass of dried ultraviolet absorber (2,2'-(1,4-phenylene)bis(4H-3,1-benzoxazinon-4-one) and 90 parts by mass of particle-free PET (A) (intrinsic viscosity 0.62 dl / g) were mixed and kneaded using an extruder to obtain polyethylene terephthalate resin (B) containing an ultraviolet absorber (hereinafter referred to as PET (B)).
[0074] (Production Example 3 - Preparation of Adhesion Modifier Coating Solution) By carrying out an ester exchange reaction and a polycondensation reaction by a conventional method, a water-dispersible sulfonate metal base-containing copolymerized polyester resin was prepared, which has a composition of 46 mol% terephthalic acid, 46 mol% isophthalic acid, and 8 mol% sodium 5-sulfonatoisophthalate as dicarboxylic acid components (relative to the total dicarboxylic acid components), 50 mol% ethylene glycol, and 50 mol% neopentyl glycol as glycol components (relative to the total glycol components). Next, 51.4 parts by mass of water, 38 parts by mass of isopropyl alcohol, 5 parts by mass of n-butyl cellosolve, and 0.06 parts by mass of a nonionic surfactant were mixed, heated and stirred, and when the temperature reached 77°C, 5 parts by mass of the water-dispersible sulfonate metal base-containing copolymerized polyester resin was added, and the mixture was stirred until no resin lumps remained, and then the resin aqueous dispersion was cooled to room temperature to obtain a uniform water-dispersible copolymerized polyester resin liquid with a solid content concentration of 5.0% by mass. Furthermore, 3 parts by mass of aggregated silica particles (manufactured by Fuji Silysia Co., Ltd., Sylysia 310) were dispersed in 50 parts by mass of water, and then 0.54 parts by mass of the aqueous dispersion of Sylysia 310 was added to 99.46 parts by mass of the above water-dispersible copolymer polyester resin liquid, and 20 parts by mass of water was added while stirring to obtain an adhesion-modifying coating liquid.
[0075] (Polarizer) A roll of a polyvinyl alcohol film having a thickness of 80 μm, which had been continuously dyed in an iodine aqueous solution, was stretched 5 times in the conveying direction and dried to obtain a long polarizer. The refractive index of the polarizer in the transmission axis direction was 1.51.
[0076] (Polarizer protection film 1) As the raw material for the intermediate layer of the base film, 90 parts by mass of PET (A) resin pellets containing no particles and 10 parts by mass of PET (B) resin pellets containing an ultraviolet absorber were dried under reduced pressure (1 Torr) at 135 ° C for 6 hours, and then fed to extruder 2 (for intermediate layer II layer), and PET (A) was dried by a conventional method and fed to extruder 1 (for outer layer I layer and outer layer III layer), respectively, and melted at 285 ° C. These two types of polymers were filtered with a stainless steel sintered filter medium (nominal filtration accuracy 10 μm particle 95% cut) and laminated in a two-type three-layer merging block, extruded into a sheet shape from a die, and then wrapped around a casting drum with a surface temperature of 30 ° C using an electrostatic casting method, cooled and solidified, and an unstretched film was made. At this time, the discharge amount of each extruder was adjusted so that the thickness ratio of I layer, II layer, and III layer was 10:80:10.
[0077] Next, a coating amount of 0.08 g / m2 was applied to both sides of the unstretched PET film by the reverse roll method. 2 After the adhesiveness-modifying coating liquid was applied so that the thickness became 100 μm, the coating was dried at 80° C. for 20 seconds.
[0078] The unstretched film with the coating layer formed was introduced into a tenter stretching machine, and while holding the ends of the film with clips, it was introduced into a hot air zone at a temperature of 125°C and stretched 4.0 times in the width direction. Next, while maintaining the width stretched in the width direction, it was treated at a temperature of 225°C for 10 seconds, and further subjected to a relaxation treatment of 3.0% in the width direction to obtain a uniaxially stretched PET film with a film thickness of about 100 μm. The Re of the obtained film was 10300 nm, Rth was 12350 nm, Re / Rth was 0.83, Nx=1.588, and Ny=1.691.
[0079] (Polarizer protection film 2) A uniaxially stretched PET film having a thickness of about 80 μm was obtained by producing the film in the same manner as in Polarizer Protective Film 1, except that the line speed was changed to change the thickness of the unstretched film. The obtained film had Re of 8080 nm, Rth of 9960 nm, Re / Rth of 0.81, Nx=1.589, and Ny=1.690.
[0080] (Polarizer protection film 3) A uniaxially stretched PET film having a thickness of about 60 μm was obtained by producing the film in the same manner as in Polarizer Protective Film 1, except that the line speed was changed to change the thickness of the unstretched film. The obtained film had Re of 6060 nm, Rth of 7470 nm, Re / Rth of 0.81, Nx=1.589, and Ny=1.690.
[0081] (Polarizer protection film 4) A uniaxially stretched PET film having a thickness of about 40 μm was obtained by producing the film in the same manner as in Polarizer Protective Film 1, except that the line speed was changed to change the thickness of the unstretched film. The obtained film had Re of 4160 nm, Rth of 4920 nm, Re / Rth of 0.85, Nx=1.587, and Ny=1.691.
[0082] (Polarizer protection film 5) An unstretched film produced in the same manner as in Polarizer Protective Film 1 was heated to 105°C using a group of heated rolls and an infrared heater, then stretched 1.5 times in the running direction using a group of rolls with different peripheral speeds, and then introduced into a hot air zone at a temperature of 130°C and stretched 4.0 times in the width direction to obtain a biaxially stretched PET film with a film thickness of approximately 100 μm in the same manner as in Polarizer Protective Film 1. The obtained film had Re of 7820 nm, Rth of 13890 nm, Re / Rth of 0.56, Nx=1.608, and Ny=1.686.
[0083] (Polarizer protection film 6) An unstretched film produced in the same manner as in Polarizer Protective Film 1 was heated to 105°C using a group of heated rolls and an infrared heater, and then stretched 2.0 times in the running direction using a group of rolls with different peripheral speeds, and then introduced into a hot air zone at a temperature of 135°C and stretched 4.0 times in the width direction to obtain a biaxially stretched PET film with a film thickness of approximately 100 μm in the same manner as in Polarizer Protective Film 1. The obtained film had Re of 6400 nm, Rth of 14600 nm, Re / Rth of 0.44, Nx=1.617, and Ny=1.681.
[0084] (Polarizer protection film 7) An unstretched film produced in the same manner as in Polarizer Protective Film 1 was heated to 105°C using a group of heated rolls and an infrared heater, and then stretched 2.8 times in the running direction using a group of rolls with different peripheral speeds, and then introduced into a hot air zone at a temperature of 140°C and stretched 4.0 times in the width direction to obtain a biaxially stretched PET film with a film thickness of approximately 100 μm in the same manner as in Polarizer Protective Film 1. The obtained film had Re of 5400 nm, Rth of 15900 nm, Re / Rth of 0.34, Nx=1.631, and Ny=1.685.
[0085] (Polarizer protection film 8) An unstretched film produced in the same manner as in Polarizer Protective Film 1 was heated to 105°C using a group of heated rolls and an infrared heater, and then stretched 3.3 times in the running direction using a group of rolls with different peripheral speeds, and then introduced into a hot air zone at a temperature of 140°C and stretched 4.0 times in the width direction to obtain a biaxially stretched PET film with a film thickness of approximately 100 μm in the same manner as in Polarizer Protective Film 1. The obtained film had Re of 4800 nm, Rth of 16700 nm, Re / Rth of 0.29, Nx=1.640, and Ny=1.688. Using the polarizer protective films 1 to 8, liquid crystal displays were produced as described below.
[0086] Example 1 A polarizer protective film 1 was attached to one side of a polarizer made of PVA and iodine so that the transmission axis of the polarizer and the fast axis of the film were parallel, and a TAC film (manufactured by Fujifilm Corporation, thickness 80 μm) was attached to the opposite side to prepare a polarizing plate 1. The polarizing plate on the viewing side of a Toshiba Corporation REGZA 43J10X was replaced with the above polarizing plate 1 so that the polyester film was on the opposite side (distal) to the liquid crystal, to prepare a liquid crystal display device. The polarizing plate 1 was replaced so that the direction of the transmission axis was the same as that of the polarizing plate before replacement.
[0087] Example 2 A polarizer protective film 2 was attached to one side of a polarizer made of PVA and iodine so that the transmission axis of the polarizer and the fast axis of the film were parallel, and a TAC film (manufactured by Fujifilm Corporation, thickness 80 μm) was attached to the opposite side to prepare a polarizing plate 2. A liquid crystal display device was prepared in the same manner as in Example 1, except that polarizing plate 1 was changed to polarizing plate 2.
[0088] Example 3 A polarizer protective film 3 was attached to one side of a polarizer made of PVA and iodine so that the transmission axis of the polarizer and the fast axis of the film were parallel, and a TAC film (manufactured by Fujifilm Corporation, thickness 80 μm) was attached to the opposite side to prepare polarizing plate 3. A liquid crystal display device was prepared in the same manner as in Example 1, except that polarizing plate 1 was changed to polarizing plate 3.
[0089] Example 4 A polarizer protective film 3 was attached to one side of a polarizer made of PVA and iodine so that the transmission axis of the polarizer and the fast axis of the film were parallel, and a TAC film (manufactured by Fujifilm Corporation, thickness 80 μm) was attached to the opposite side to prepare a polarizing plate 3. The polarizing plate on the light source side of a Toshiba Corporation REGZA 43J10X was replaced with the above polarizing plate 3 so that the polyester film was on the opposite side (distal) to the liquid crystal, to prepare a liquid crystal display device. The polarizing plate 3 was replaced so that the direction of the transmission axis was the same as that of the polarizing plate before replacement.
[0090] Example 5 A polarizer protective film 3 was attached to one side of a polarizer made of PVA and iodine so that the transmission axis of the polarizer and the fast axis of the film were parallel, and a TAC film (manufactured by Fujifilm Corporation, thickness 80 μm) was attached to the opposite side to prepare a polarizing plate 3. The polarizing plates on the viewing side and light source side of a Toshiba Corporation REGZA 43J10X were replaced with the above polarizing plate 3 so that the polyester film was on the opposite side (distal) to the liquid crystal, to prepare a liquid crystal display device. The polarizing plate 3 was replaced so that the direction of the transmission axis was the same as that of the polarizing plate before replacement.
[0091] Example 6 A polarizer protective film 4 was attached to one side of a polarizer made of PVA and iodine so that the transmission axis of the polarizer and the fast axis of the film were parallel, and a TAC film (manufactured by FUJIFILM Corporation, thickness 80 μm) was attached to the opposite side to prepare polarizing plate 4. A liquid crystal display device was prepared in the same manner as in Example 1, except that polarizing plate 1 was changed to polarizing plate 4.
[0092] Example 7 A polarizer protective film 5 was attached to one side of a polarizer made of PVA and iodine so that the transmission axis of the polarizer and the fast axis of the film were parallel, and a TAC film (manufactured by FUJIFILM Corporation, thickness 80 μm) was attached to the opposite side to prepare polarizing plate 5. A liquid crystal display device was prepared in the same manner as in Example 1, except that polarizing plate 1 was changed to polarizing plate 5.
[0093] Example 8 A polarizer protective film 6 was attached to one side of a polarizer made of PVA and iodine so that the transmission axis of the polarizer and the fast axis of the film were parallel, and a TAC film (manufactured by FUJIFILM Corporation, thickness 80 μm) was attached to the opposite side to prepare polarizing plate 6. A liquid crystal display device was prepared in the same manner as in Example 1, except that polarizing plate 1 was changed to polarizing plate 6.
[0094] Comparative Example 1 A polarizer protective film 1 was attached to one side of a polarizer made of PVA and iodine so that the transmission axis of the polarizer and the fast axis of the film were perpendicular, and a TAC film (manufactured by Fujifilm Corporation, thickness 80 μm) was attached to the opposite side to prepare a polarizing plate 7. The polarizing plate on the viewing side of a Toshiba Corporation REGZA 43J10X was replaced with the above polarizing plate 7 so that the polyester film was on the opposite side (distal) to the liquid crystal, to prepare a liquid crystal display device. The polarizing plate 7 was replaced so that the direction of the transmission axis was the same as that of the polarizing plate before replacement.
[0095] Comparative Example 2 A polarizer protective film 2 was attached to one side of a polarizer made of PVA and iodine so that the transmission axis of the polarizer and the fast axis of the film were perpendicular to each other, and a TAC film (manufactured by Fujifilm Corporation, thickness 80 μm) was attached to the opposite side to prepare a polarizing plate 8. A liquid crystal display device was prepared in the same manner as in Comparative Example 1, except that polarizing plate 7 was changed to polarizing plate 8.
[0096] Comparative Example 3 A polarizer protective film 3 was attached to one side of a polarizer made of PVA and iodine so that the transmission axis of the polarizer and the fast axis of the film were perpendicular to each other, and a TAC film (manufactured by Fujifilm Corporation, thickness 80 μm) was attached to the other side to prepare a polarizing plate 9. A liquid crystal display device was prepared in the same manner as in Comparative Example 1, except that polarizing plate 7 was changed to polarizing plate 9.
[0097] Comparative Example 4 A polarizer protective film 3 was attached to one side of a polarizer made of PVA and iodine so that the transmission axis of the polarizer and the fast axis of the film were perpendicular, and a TAC film (manufactured by Fujifilm Corporation, thickness 80 μm) was attached to the opposite side to prepare a polarizing plate 9. The polarizing plate on the light source side of a Toshiba Corporation REGZA 43J10X was replaced with the above polarizing plate 9 so that the polyester film was on the opposite side (distal) to the liquid crystal, to prepare a liquid crystal display device. The polarizing plate 9 was replaced so that the direction of the transmission axis was the same as that of the polarizing plate before replacement.
[0098] Comparative Example 5 A polarizer protective film 3 was attached to one side of a polarizer made of PVA and iodine so that the transmission axis of the polarizer and the fast axis of the film were perpendicular, and a TAC film (manufactured by Fujifilm Corporation, thickness 80 μm) was attached to the other side to prepare a polarizing plate 9. The polarizing plates on the viewing side and light source side of a Toshiba Corporation REGZA 43J10X were replaced with the above polarizing plate 9 so that the polyester film was on the opposite side (distal) to the liquid crystal, to prepare a liquid crystal display device. The polarizing plate 9 was replaced so that the direction of the transmission axis was the same as that of the polarizing plate before replacement.
[0099] Comparative Example 6 A polarizer protective film 4 was attached to one side of a polarizer made of PVA and iodine so that the transmission axis of the polarizer and the fast axis of the film were perpendicular to each other, and a TAC film (manufactured by Fujifilm Corporation, thickness 80 μm) was attached to the opposite side to prepare a polarizing plate 10. A liquid crystal display device was prepared in the same manner as in Comparative Example 1, except that polarizing plate 7 was replaced with polarizing plate 10.
[0100] Comparative Example 7 A polarizer protective film 7 was attached to one side of a polarizer made of PVA and iodine so that the transmission axis of the polarizer and the fast axis of the film were parallel, and a TAC film (manufactured by Fujifilm Corporation, thickness 80 μm) was attached to the opposite side to prepare a polarizing plate 11. A liquid crystal display device was prepared in the same manner as in Comparative Example 1, except that polarizing plate 7 was replaced with polarizing plate 11.
[0101] Comparative Example 8 A polarizer protective film 8 was attached to one side of a polarizer made of PVA and iodine so that the transmission axis of the polarizer and the fast axis of the film were parallel, and a TAC film (manufactured by Fujifilm Corporation, thickness 80 μm) was attached to the opposite side to prepare a polarizing plate 12. A liquid crystal display device was prepared in the same manner as in Comparative Example 1, except that polarizing plate 7 was changed to polarizing plate 12.
[0102] The liquid crystal display devices obtained in the respective Examples were subjected to measurement of rainbow spots, and the results are shown in Table 1 below.
[0103] [Table 1] [Industrial Applicability]
[0104] INDUSTRIAL APPLICABILITY The liquid crystal display device and polarizing plate of the present invention can ensure good visibility with the occurrence of rainbow-like color spots significantly suppressed at any observation angle, and thus have extremely high industrial applicability.
Claims
1. A liquid crystal display device having a backlight source, two polarizing plates, and a liquid crystal cell disposed between the two polarizing plates, The backlight light source is a white light source having an emission spectrum with peak tops in the wavelength ranges of 400 nm or more and less than 495 nm, 495 nm or more and less than 600 nm, and 600 nm or more and 780 nm or less, and a half-width of the peak with the highest peak intensity in the wavelength range of 600 nm or more and 780 nm or less is less than 5 nm, or 4+ The phosphor comprises an activated fluoride complex phosphor, and has a peak top of an emission spectrum in each of the wavelength regions of 400 nm or more and less than 495 nm, 495 nm or more and less than 600 nm, and 600 nm or more and 780 nm or less, and the peak in the wavelength region of 600 nm or more and 780 nm or less is the Mn 4+ a white light source derived from an activated fluoride complex phosphor; At least one of the polarizing plates on the viewing side has a polyester film having an in-plane retardation of 7820 nm or less laminated on at least one surface of a polarizer, and the refractive index of the polyester film in a direction parallel to the transmission axis of the polarizer is 1.53 to 1.
62. LCD display device.
2. The emission spectrum of the backlight light source is The half-width of the peak with the highest peak intensity in the wavelength region of 400 nm or more and less than 495 nm is 5 nm or more, The half-width of the peak with the highest peak intensity in the wavelength region of 495 nm or more and less than 600 nm is 5 nm or more. The liquid crystal display device according to claim 1 .
3. The Mn 4+ The activated fluoride complex phosphor is K2SiF6:Mn 4+ 2. The liquid crystal display device according to claim 1,
4. 4. The liquid crystal display device according to claim 1, wherein the polyester film has a thickness of 60 μm or less.
5. The refractive index of the polyester film in a direction parallel to the transmission axis of the polarizer is 1.53 to 1.61; 4. The liquid crystal display device according to claim 1, wherein the polyester film has an Re / Rth of 0.2 to 0.
85.
6. 4. The liquid crystal display device according to claim 1, wherein the in-plane retardation of the polyester film is 4160 to 7820 nm.
7. 7. The liquid crystal display device according to claim 1, wherein a difference between a refractive index of the polarizer in the transmission axis direction and a refractive index of the polyester film in a direction parallel to the transmission axis of the polarizer is 0.12 or less.
8. A polarizing plate having a polyester film laminated on at least one surface of a polarizer, The in-plane retardation of the polyester film is 7820 nm or less, The thickness of the polyester film is 60 μm or less, The polyester film has a refractive index of 1.53 to 1.608 in a direction parallel to the transmission axis of the polarizer.
9. A polarizing plate having a polyester film laminated on at least one surface of a polarizer, The in-plane retardation of the polyester film is 7820 nm or less, The polyester film has a Re / Rth of 0.2 to 0.85; The polyester film has a refractive index of 1.53 to 1.61 in a direction parallel to the transmission axis of the polarizer.
Citation Information
Patent Citations
Optical film, polarizing plate using the same, method for producing the same and liquid crystal display
JP2002116320A
Polarizing plate and its manufacturing method, and liquid crystal display device using the same
JP2004205773A
Polarizing plate protective film, and polarizing plate and liquid crystal display device using the same,
JP2004219620A
Polarizer and liquid crystal display device
JP2012203211A
Optical film, polarizing plate, liquid crystal panel, and image display device
JP2014016476A